A shaped reflector antenna for 60-GHz radio access points. - Smulders, P.F.M (IEEE Transactions on antennas and propagation)
A shaped reflector antenna for a prototype 60-GHz wireless LAN access point has been designed and constructed. Its performance has been verified through measurements of the antenna far-field radiation patterns in the compact antenna test range. Near-field patterns have been reconstructed from the measured far-field data by using the Hankel transform. The results show that the amplitude across the footprint area remains within 6 dB of uniformity